2023
DOI: 10.1128/mbio.00295-23
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Produced Lysogenic Phages Are an Important Component of the Soybean Bradyrhizobium Mobilome

Abstract: Previous studies have shown that IS and plasmids mediate HGT of symbiotic nodulation ( nod ) genes in soybean bradyrhizobia; however, these events require close cell-to-cell contact, which could be limited in soil environments. Bacteriophage-assisted gene transduction through spontaneously produced prophages provides a stable means of HGT not limited by the constraints of proximal cell-to-cell contact.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Interspecific competition between maizesoybean intercropping leads to more efficient utilization of applied N (Zhang et al, 2023). Adding Bradyrhizobium with these three micronutrients zinc, iron, and molybdenum have resulted in a remarkable yield response in soybean as reported earlier by Tiwari et al (2018) and Joglekar et al (2023). Furthermore, Mo can influence the interaction between maize and soybean in intercropping systems, potentially impacting overall crop productivity and quality (Abendroth et al, 2017;Oliveira et al, 2022).…”
Section: Introductionmentioning
confidence: 78%
“…Interspecific competition between maizesoybean intercropping leads to more efficient utilization of applied N (Zhang et al, 2023). Adding Bradyrhizobium with these three micronutrients zinc, iron, and molybdenum have resulted in a remarkable yield response in soybean as reported earlier by Tiwari et al (2018) and Joglekar et al (2023). Furthermore, Mo can influence the interaction between maize and soybean in intercropping systems, potentially impacting overall crop productivity and quality (Abendroth et al, 2017;Oliveira et al, 2022).…”
Section: Introductionmentioning
confidence: 78%
“…In addition, studies have shown that type VI secretion systems ( Bladergroen et al., 2003 ; De Campos et al., 2017 ) as well as the production of phages ( Schwinghamer and Brockwell, 1978 ; Joglekar et al., 2023 ) or bacteriocins ( Hirsch, 1979 ; Triplett and Barta, 1987 ; Oresnik et al., 1999 ) in rhizobia can play an important role in the direct inhibition of bacterial competitors. Among antagonistic molecules produced by rhizobia, diffusible quorum sensing molecules, in particular Acyl Homoserine Lactones (AHLs), can inhibit the growth of other rhizobial strains by activating LuxR-type regulators in the neighbouring strains and inducing genes leading to growth arrest ( Schripsema et al., 1996 ; Wilkinson et al., 2002 ).…”
Section: The Rhizosphere Microbiome: a Hotspot For Microbial Interact...mentioning
confidence: 99%